Tourist motivation and revisitation in Jeju during COVID-19: Insights and post-pandemic implications - Hwa-soon Lim; Mona Chang (Global Business & Finance Review (GBFR), 2024)
Purpose: This study aims to identify controllable factors influencing domestic tourists' revisits, taking into account concerns and desires related to travel to inform domestic tourism marketing strategies. Design/methodology/approach: The study gathered data through a preliminary survey of 930 participants who had visited Jeju Island in February 2022. It utilized analytical methods like factor analysis and structural equation modeling (PLS-SEM) to assess the factors influencing revisits by domestic tourists. Findings: Emotional and cognitive factors significantly influence behavioral intentions, with the perceived risk of the pandemic having a paradoxical effect, positively impacting attitudes and revisit intentions despite stimulating negative emotions and anxiety among tourists, consistent with the observed surge in domestic tourist numbers on Jeju Island. Research limitations/implications: Limitations of this study include distinguishing between motivations for domestic and international tourism in crisis situations and highlighting the importance of conducting in-depth socio-demographic analyses for better understanding. This study identifies travel motivations within specific cultural groups and informs destination management and tourism resource development strategies. Originality/value: This study's innovative blend of the S-O-R model and Theory of Reasoned Action provides key insights into tourist behavior. The findings on Jeju Island's resilience as a domestic tourist destination during the COVID-19 pandemic have crucial implications, emphasizing the need for ongoing efforts to enhance tourists' experiences and adapt to changing external factors in the tourism industry.
Keywords: 650; Travel motivation; Revisit intention; Post COVID-19; Stimulus-Organism-Response model; Theory of Reasoned Action